2017
DOI: 10.1159/000478259
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Alpha-Actinin-4 Is Upregulated in Women with Threatened Preterm Labor and Microbial Invasion of the Amniotic Cavity

Abstract: Objective: To characterize the proteome profile of women with threatened preterm labor (PTL) below 34;0 weeks with and without microbial invasion of the amniotic cavity (MIAC) using mass spectrometry in the amniotic fluid (AF) and Western blot analysis in the cervical mucus and the vaginal fluid. Subjects and Methods: In the discovery phase, a case-control study including 8 women with MIAC and 7 without matched for gestational age at sampling was performed. Proteomic profile characterization was done using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…The precision and accuracy of the nine ELISAs were validated for plasma samples before use through spike‐and‐recovery and linearity‐of‐dilution experiments, which revealed their good performance. These proteins were selected to be explored in the present study because (i) they were previously suggested to be useful blood biomarkers for the detection of histologic inflammation in the placenta; however, whether their altered expression in the plasma is associated with AF inflammation/infection and adverse neonatal outcomes in the context of PPROM remains unclear [22, 23]; (ii) they could have potential clinical significance in the maternal blood regarding the outcomes of interest herein investigated, considering previous proteomic profiling studies that suggested that they could be potential candidates biomarkers for MIAC, IAI, or preterm birth [18, 2426, 28, 32]; and because (iii) their related signaling pathways (such as inflammation/immune‐, cell adhesion, and ECM homeostasis [https://www.uniprot.org/]) are known to be involved in the pathogenesis of adverse pregnancy and neonatal outcomes [33–36].…”
Section: Methodsmentioning
confidence: 99%
“…The precision and accuracy of the nine ELISAs were validated for plasma samples before use through spike‐and‐recovery and linearity‐of‐dilution experiments, which revealed their good performance. These proteins were selected to be explored in the present study because (i) they were previously suggested to be useful blood biomarkers for the detection of histologic inflammation in the placenta; however, whether their altered expression in the plasma is associated with AF inflammation/infection and adverse neonatal outcomes in the context of PPROM remains unclear [22, 23]; (ii) they could have potential clinical significance in the maternal blood regarding the outcomes of interest herein investigated, considering previous proteomic profiling studies that suggested that they could be potential candidates biomarkers for MIAC, IAI, or preterm birth [18, 2426, 28, 32]; and because (iii) their related signaling pathways (such as inflammation/immune‐, cell adhesion, and ECM homeostasis [https://www.uniprot.org/]) are known to be involved in the pathogenesis of adverse pregnancy and neonatal outcomes [33–36].…”
Section: Methodsmentioning
confidence: 99%
“… 8 Cervical α-actinin-4 increased in patients with preterm delivery. 9 However, none of these markers can predict premature delivery in the early stage of pregnancy. Therefore, this study aimed to identify serum markers that can predict preterm delivery at an earlier stage of pregnancy.…”
Section: Introductionmentioning
confidence: 99%